The trick of the tail: protein-protein interactions of metabotropic glutamate receptors. - Enz, Ralf (Bioessays, 2007)
It was initially believed that G-protein-coupled receptors, such as metabotropic glutamate receptors, could simply be described as individual proteins that are associated with intracellular signal cascades via G-proteins. This view is no longer tenable. Today we know that metabotropic glutamate receptors (mGluRs) can dimerize and bind to a variety of proteins in addition to trimeric G-proteins. These newly identified protein interactions led to the discovery of new regulatory mechanisms that are independent of and sometimes synergistic with the classical G-protein-coupled second messenger pathways. Notably, several of these mechanisms connect mGluR-mediated signaling to other receptor classes, thereby creating a network of different receptor types and associated signal cascades. The intracellular C-termini of mGluRs play a key role in the regulation of these networks, and various new protein interactions of these domains were described recently. Because mGluRs are involved in a variety of physiological and pathophysiological processes, some of the proteins interacting with this receptor class have potential as valuable pharmaceutical targets. This review will give a comprehensive overview of proteins interacting with mGluR C-termini, highlight new evolving regulatory mechanisms for glutamatergic signal transduction and discuss possibilities for future drug development. © 2006 Wiley Periodicals, Inc.
UnivIS-Import:2017-12-18:Pub.2007.med.IB.profes_1.thetri